School life of secondary education reform: polarizations, disputes and challenges (Praxis Educativa, 2020)
The political question of the Educational reforms, their legacies and impact on the life of schools is becoming increasingly more relevant and it has been installed on the educational research agenda (Cantero and Celman, 2006; Frigerio, 2000; Giovine, 2008; Gorostiaga and Tello, 2011; Grinberg, 2008; Miranda, 2001; Tiramonti 2015).We describe meanings and effects of a secondary education reform with a focus on school daily life, and structuring logics that polarize teachers and students. However, we also observe how teachers develop multiple strategies for students’ inclusion and learning. We thus problematize the tension between a few effects that evidence polarizations and disputes on the objectives and the modes of policy anda series ofchallenges that denotes the political character of education and places students as subjects of rights.
Keywords: reform-school life-high education-inclusion